(untitled) (Research, Society and Development, 2025)
Objective: To map the tools and strategies applied in pharmaceutical services and/or pharmaceutical care for elderly individuals with polymorbidities, polypharmacy, and hearing impairment in the context of health education. Methodology: This is a scoping review following the guidelines established by the JBI, guided by the acronym PCC in which: Participants: Elderly individuals with polymorbidities, polypharmacy, and hearing impairment; Concept: Educational Strategies and Tools; Context: Pharmaceutical Services and/or Pharmaceutical Care. The expected time frame was from 2020 to 2024, published in Portuguese, Spanish, and English. Scientific databases, repositories of scientific articles, and Google Scholar were used. Results: six articles met the inclusion criteria. The studies summarize the specificities of the demands of elderly patients with polymorbidities, polypharmacy, and hearing impairment, highlighting the measures and tools implemented in health services for this population, from the perspective of what is recommended and what is found in the practice of pharmaceutical services for effective communication with the patient. Conclusion: Elderly patients with hearing impairment who present a picture of polymorbidities and consequent polypharmacy have needs which Goes beyond purely pharmaceutical knowledge. They are required to understand cultural and linguistic aspects and demand specific pharmaceutical care strategies.